Объяснение:
SnO + 2HCl = SnCl2 + H2O
SnO + 2H(+) + 2Cl(-) = Sn(2+) + 2Cl(-) + H2O
SnO + 2H(+) = Sn(2+) + H2O
SnCl2 + 2NaOH = Sn(OH)2↓ + 2NaCl
Sn(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = Sn(OH)2↓ + 2Na(+) + 2Cl(-)
Sn(2+) + 2OH(-) = Sn(OH)2↓
Sn(OH)2 + H2SO4 = SnSO4 + 2H2O
Sn(OH)2 + 2H(+) + SO4(2-) = Sn(2+) + SO4(2-) + 2H2O
Sn(OH)2 + 2H(+) = Sn(2+) + 2H2O
SnSO4 + BaCl2 = BaSO4↓ + SnCl2
Sn(2+)+ SO4(2-) + Ba(2+) + 2Cl(-) = BaSO4 ↓+ Sn(2+) + 2Cl(-)
Ba(2+) + SO4(2-) = BaSO4↓
BaSO4 + 2NaOH = Ba(OH)2 + Na2SO4
BaSO4 + 2Na(+) + 2OH(-) = Ba(2+) + 2OH(-) + 2Na(+) + SO4(2-)
BaSO4 = Ba(2+) + SO4(2-)
А)CaCl2+K2CO3=CaCO3+2 KCl
Ca(2+)+2 Cl(-)+2 K(+)+CO3(2-)=CaCO3+2 K(+)+2 Cl(-)
Ca(2+)+CO3(2-)=CaCO3
B) Данная реакция не идёт так как все вещества растворимы а надо хотя бы чтоб одно было нерастворимым
C)K2SiO3+2 HCl=2 KCl+SiO2↓+H2O
2 K(+)+SiO3(2-)+2 H(+)+2 Cl(-)=2 K(+)+2 Cl(-)+SiO2↓+H2O
2 H(+)+SiO3(2-)=SiO2↓+H2O
D)H3PO4+3 NaOH=Na3PO4+3 H2O
3 H(+)+PO4(3-)+3 Na(+)+3 OH(-)=3 Na(+)+PO4(3-)+3 H2O
3 H(+)+3 OH(-)=3H2O